New electronically adjustable memelement emulator for realizing the behaviour of fully-floating meminductor and memristor. (August 2021) - Bhardwaj, Kapil; Srivastava, Mayank
Abstract: The memelements have gained a significant interest due to the useful hysteresisproperty; they exhibit in their transient characteristics. Based ondifferent pairs of electrical quantities (current, voltage, charge, and flux), they relate, memelements are classified as; memristor, meminductor and memcapacitor respectively. This work proposes a Fully-floating memelement emulator to realize the behaviour of a memristor and meminductor by using the optimum number of circuit resources. This memelement emulator has been designed by using just two VDTAs (Voltage Differencing Transconductance Amplifiers) with only two grounded passive elements. The designed circuit also possesses the feature of electronic tunability, which provides the controllable nature of realized floating inverse meminductance and memconductance. As per the knowledge of the authors, no such compact meminductor emulator has been reported so far, which does not require an external voltage multiplier and owns such useful features. The applicability of the suggested memelement emulator has also been shown for both the realized elements in neural network applications. The simulations have been performedunder PSPICE environment using CMOS technology for verification of the designed circuits. Finally, the commercial IC-based realization of the proposed memelement emulator has been discussed and results have been presented.